The Urgency of Ratification of the International Convention for the Protection of All Persons from Enforced Disappearance in the Enforcement of Human Rights in Indonesia - Monalisa Indah Ronauli; Gelar Ali Ahmad (NOVUM : JURNAL HUKUM, 2025)
The mechanism of enforced disappearance is regulated in Law No. 39 Year 1999 on Human Rights and Law No. 26 Year 2000 on Human Rights Court, but in the law the definition of enforced disappearance is still unclear, there is no active subject and there is no element of degrading human dignity in crimes against humanity. This study was conducted to analyze the urgency of ratification of the International Convention For The Protection Of All Persons From Enforced Disappearance (ICPPED) in upholding human rights in Indonesia and to examine the legal protection of victims and families of victims of enforced disappearance. This research uses normative juridical research method by using laws and regulations and legal science concepts as the basis of analysis. As for the research results obtained, ratifying the International Convention For The Protection Of All Persons From Enforced Disappearance (ICPPED) was carried out as an effort to break the chain of enforced disappearance practices, anti-impunity, and as an effort to provide guarantees of recovery for victims of enforced disappearance. Legal protection is provided as a form of strengthening regulations and as an effort to favor victims in the form of restoring the rights of victims of deprived rights protection including restitution, compensation, and rehabilitation.